Labour data collection - Grandin, B.E. (International Livestock Centre for Africa, 1983)
Discusses issues related to the collection of data on labour inputs for pastoral production, considering the utility of data on labour as part of pastoral systems research, and research methods for data collection, particularly for multi-visit recall techniques and the time allocation technique.